2021
DOI: 10.1177/01968599211043403
|View full text |Cite
|
Sign up to set email alerts
|

Degrading Bodies in Pandemic Times: Politicizing Cruelty During the COVID-19 and Obesity Crises

Abstract: Mass communications frame fatness and COVID-19 as a dual threat. This discourse furthers well-established tendencies to degrade bodies labelled overweight or obese, positioning them as deficient and requiring correction. Empirically, this article draws from an online US right-wing news media platform, Campus Reform, including readers’ comments (n = 135) on an article denouncing professors working in fat studies during the COVID-19 lockdown. This status degradation ceremony—backed by ‘big money’ that funds camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
(42 reference statements)
0
9
0
2
Order By: Relevance
“…Overall, in the scientific literature, public health pronouncements, and wider discourse, narratives around personal responsibility and the stigmatization of fat bodies have had significant uptake (Monaghan, 2021 ). However, there has also been resistance to these narratives in varying degrees: some have attempted to move away from personal responsibility and blame while maintaining that obesity is an inherently risky biological category, whilst others have taken up structural fatphobia as a cause of disparities in the burden of Covid-19.…”
Section: Fatness and Health Disparities In The Context Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, in the scientific literature, public health pronouncements, and wider discourse, narratives around personal responsibility and the stigmatization of fat bodies have had significant uptake (Monaghan, 2021 ). However, there has also been resistance to these narratives in varying degrees: some have attempted to move away from personal responsibility and blame while maintaining that obesity is an inherently risky biological category, whilst others have taken up structural fatphobia as a cause of disparities in the burden of Covid-19.…”
Section: Fatness and Health Disparities In The Context Of Covid-19mentioning
confidence: 99%
“…Although some social sciences and humanities scholarship has emerged that attends to structural fat discrimination in the context of Covid-19 (Bessey & Brady, 2021 ; McPhail & Orsini, 2021 ; Monaghan, 2021 ; Pausé et al, 2021a , 2021b ), overall, this narrative of structural fat discrimination has received far less attention than those which hold onto fatness as a biological category, whether that be coupled with personal responsibility and blame or highlighting the negative effects of weight stigma.…”
Section: Fatness and Health Disparities In The Context Of Covid-19mentioning
confidence: 99%
“…Algunos estudios recientes sugieren que, con motivo de la pandemia por COVID-19, los mensajes difundidos por los medios acentuaron la representación de estigmatización y discriminación por sobrepeso (Flint, 2020;Monaghan, 2021;Stewart y Ogden, 2022), ya que casi desde el principio de la pandemia se asoció un mayor índice de masa corporal con un riesgo más elevado de enfermedad grave y muerte por coronavirus. En una situación pandémica que ya de por sí aumentó de forma generalizada la ansiedad entre la población, esta asociación problematizó aún más el sobrepeso y contribuyó a aumentar la ansiedad entre las personas con obesidad en mayor medida que entre el resto.…”
Section: Introductionunclassified
“…Historical experience has shown that certain stigma narratives always emerge in the initial stages of outbreaks [ 17 , 20 , 21 , 22 , 23 , 24 ]. Stigma is often associated with the use of specific media framing strategies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In the era of the COVID-19 pandemic, prejudice against Chinese and Asian people has proliferated in American society [ 1 , 23 , 28 , 33 , 34 ] as online media have favored biased news frames to label China as the predominant “source” of the coronavirus.…”
Section: Introductionmentioning
confidence: 99%